2008
DOI: 10.2215/cjn.00500108
|View full text |Cite
|
Sign up to set email alerts
|

High-Dosage Intravenous Immunoglobulin–Associated Macrovacuoles Are Associated with Chronic Tubulointerstitial Lesion Worsening in Renal Transplant Recipients

Abstract: Design, setting, participants, & measurements: Twenty-seven kidney transplant recipients who had high immunologic risk and were treated with four courses of IVIg after transplantation were studied retrospectively at a transplant center, and findings were compared with those of 27 control subjects. Protocol kidney biopsies were performed at time of transplantation and at 3 mo and 1 yr after transplantation.Results: No episode of IVIg-related acute renal failure occurred. Nevertheless, screening biopsies reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
7
1
2
Order By: Relevance
“…As previously described by our team [26], histological analysis of the kidney transplant screening biopsies revealed two different patterns of tubular vacuolization: macro-and microvacuoles ( Fig. 1a) mainly localized in the proximal tubular cells.…”
Section: Sucrose-free Ivig Formulations Are Clinically Well Toleratedsupporting
confidence: 69%
See 2 more Smart Citations
“…As previously described by our team [26], histological analysis of the kidney transplant screening biopsies revealed two different patterns of tubular vacuolization: macro-and microvacuoles ( Fig. 1a) mainly localized in the proximal tubular cells.…”
Section: Sucrose-free Ivig Formulations Are Clinically Well Toleratedsupporting
confidence: 69%
“…Finally, other factors associated with tubular toxicity, as colloid and mannitol therapy or IV contrast administration, were not available for the study. However, a previous study showed no association between iodinated contrast agents before transplantation and macrovacuoles [26]. To conclude, our results show that high-dose, sucrose-free IVIg treatment in the early post-transplantation period is clinically safe and is not associated with histological lesions in the majority of kidney recipients.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A retrospective study utilizing histologic examination of systematic serial biopsy specimens from kidney transplant recipients with high immunological risk revealed tubular macrovacuoles in 17 of 27 (63%) patients following treatment with glucose- (Endobulin) and/or maltose- (Octagam) containing IVIGs, compared with none of 27 control patients not receiving IVIG [55]. These results were obtained despite an absence of acute renal failure in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…In group A, however, no patient experienced CMV activation. IVIG were administered at a low dose, preserving safety and efficacy, in the absence of side effects, as reported in literature [5]. The mechanism of action of rituximab in antibody-mediated rejection is not clear, given that the plasma cells do not express CD20 on their surface [6].…”
Section: Discussionmentioning
confidence: 99%